Daptomycin and Its Immunomodulatory Effect: Consequences for Antibiotic Treatment of Methicillin-Resistant Staphylococcus aureus Wound Infections after Heart Surgery - Tirilomis, Theodor (Frontiers in Immunology, 2014)
Infections by methicillin-resistant Staphylococcus aureus (MRSA) play an increasing role in the postoperative course. Although wound infections after cardiac surgery are rare, the outcome is limited by prolonged treatment with high mortality. Not only surgical debridement is crucial, but also antibiotic support. Next to vancomycin and linezolid, daptomycin gains increasing importance. Although clinical evidence is limited, daptomycin has immunomodulatory properties, resulting in the suppression of cytokine expression after host immune response stimulation by MRSA. Experimental studies showed an improved efficacy of daptomycin in combination with administration of vitamin E before infecting wounds by MRSA.